TEACHERS’ CHALLENGES TO INTEGRATE ICT IN EFL TEACHING AND LEARNING ACTIVITIES - Champa, Rea Aisha; Rochsantiningsih, Dewi; Kristiana, Diah (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
By means of the innovations in Information and Communication Technology, people are able to rapidly learn and transfer information.. Keeping up with those innovations, the integration of ICT in education is the demand of time at present as ICT is being used in many other sectors all over the world. It urges the teachers to be skillful in operating ICT during their teaching.  However, there are some barriers for the teachers that prevent them to use ICT in the classroom. This paper is intended to explore the challenges of English teachers in integrating ICT into their teaching. To gain an in-depth result, this case study focuses on the interview of some English teachers in a certain school in Surakarta. The analysis of the data revealed that the barriers of English teachers in integrating ICT are lack of: ICT integration training, competence, equipment, and appropriate software and materials.